2000
DOI: 10.1097/00000372-200012000-00002
|View full text |Cite
|
Sign up to set email alerts
|

A Zonal Comparison of MIB1-Ki67 Immunoreactivity in Benign and Malignant Melanocytic Lesions

Abstract: Differentiation between malignant melanomas and benign nevi can sometimes be difficult by conventional histopathology, and additional diagnostic markers may be helpful. This study investigated the immunoreactivity of the cell proliferation marker MIB1-Ki67 in 23 compound nevi, 17 dysplastic nevi, 8 Spitz nevi (SN), and 24 malignant melanomas (MMs) and evaluated its ability in separating benign nevi from MMs. In each lesion, the average number (percentage) of MIB1-positive nuclei (%MIB1-Mean) and the maximal nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
61
0
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(71 citation statements)
references
References 37 publications
6
61
0
4
Order By: Relevance
“…16,17,22,41 Nagasaka et al 16 found that all Spitz nevi had a relatively low MIB-1 index (mean 3.2%), which was significantly lower than that of malignant melanoma (mean 15.3%). Similarly, Kanter-Lewensohn et al 17 found an average MIB-1 index of 4% in Spitz nevi and 29.7% in malignant melanoma and Bergman et al 22 reported 1.5% for Spitz nevi vs 14.9% for malignant melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…16,17,22,41 Nagasaka et al 16 found that all Spitz nevi had a relatively low MIB-1 index (mean 3.2%), which was significantly lower than that of malignant melanoma (mean 15.3%). Similarly, Kanter-Lewensohn et al 17 found an average MIB-1 index of 4% in Spitz nevi and 29.7% in malignant melanoma and Bergman et al 22 reported 1.5% for Spitz nevi vs 14.9% for malignant melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining with Ki-67, [31][32][33][34] Ki-67 and bcl-2, 35 and proliferating cell nuclear antigen 36,37 has shown some promise in discrim-inating melanoma from benign nevi, including Spitz nevi. In situ hybridization to detect expression of melastatin, 38 a melanocyte specific gene that is expressed in melanoma at levels inversely proportional to metastatic rates, is useful in predicting metastasis and disease free survival in adult patients with melanoma 39 and may be useful in predicting which atypical spitzoid lesion may be malignant.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Within this broad field, the study of the physiological and transcriptional differences between more superficial and deeper melanoma cells has emerged as an active area of research. [6][7][8] Our study aims to contribute to the understanding of intralesional differences in protein expression by malignant cells.…”
mentioning
confidence: 99%